Obesity, Adipose Tissue, and Inflammation Answered in Questions - Vanessa A. Guerreiro; Davide Carvalho; Paula Freitas (Journal of Obesity)
Background. Obesity is a global health problem of epidemic proportions, which is characterized by increased adipose tissue (AT) mass and significant repercussions in different body apparati and systems. AT is a special connective tissue, which contains several types of cells, in addition to adipocytes, and is a highly active endocrine and immune organ, which directly modulates many processes, including energy balance, metabolism, and inflammation. Summary. In this paper, the authors list and attempt to answer in a brief and simple way several questions regarding the complex relationships between obesity, adipose tissue, and inflammation, with the objective to provide an easy way to understand the main changes that occur in this pathological state. The questions are the following: Is adipose tissue only made up of adipocytes? Are adipocytes just a reservoir of free fatty acids? Do different types of fatty tissue exist? If so, which types? Can we further subcategorize the types of adipose tissue? Is it possible to form new adipocytes during adulthood? What is the role of inflammation? What is the role of macrophages? Are macrophages central mediators of obesity-induced adipose tissue inflammation and insulin resistance? What causes macrophage infiltration into adipose tissue? What is the role of hypoxia in AT alterations? Is there cross talk between adipocytes and immune cells? What other changes occur in AT in obesity? Does metabolically healthy obesity really exist? Is this a benign condition? Key messages. Obesity is a complex disease with numerous metabolic consequences, which are mainly the result of dysfunction that occurs in the adipose tissue of patients with this pathology. Understanding the pathophysiology of AT and the changes that occur in obesity would contribute to a better approach to patients with obesity, with the inherent medical implications that could result from this.